2020
DOI: 10.36489/nursing.2020v23i263p3693-3697
|View full text |Cite
|
Sign up to set email alerts
|

Causa de mortalidade materna na região metropolitana I no triênio 2013-2015, Belém, PA

Abstract: Objetivo: estudo sobre a ocorrência de óbitos maternos na região metropolitana de Belém no perí­odo de janeiro de 2013 a dezembro de 2015. Método: Trata-se de uma abordagem epidemiológica, descritiva, quantitativa, retrospectiva e documental. Incluindo: óbitos classificados como morte materna por causas obstétricas diretas e indiretas. Sendo excluí­do: óbitos classificados como acidentais. Por intermédio da estatí­stica descritiva. Resultado: No perí­odo de janeiro de 2013 a dezembro de 2015, foram declarados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Studies have shown that territories with better coverage rates have better health indicators considering that they promote the population's access to services, which helps correct inequalities. (7,8,11) It is worth noting that this study was conducted in the first year of the coronavirus 2019 pandemic. Access to prenatal care worsened during the pandemic period, which may have impacted the care for pregnant women.…”
Section: ❚ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that territories with better coverage rates have better health indicators considering that they promote the population's access to services, which helps correct inequalities. (7,8,11) It is worth noting that this study was conducted in the first year of the coronavirus 2019 pandemic. Access to prenatal care worsened during the pandemic period, which may have impacted the care for pregnant women.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…(2,3) Maternal mortality can be considered a social phenomenon because it is related to a population's living conditions and access to qualified healthcare services, and no homogeneous distribution of mortality has been observed among Brazilian regions. (4)(5)(6)(7)(8)(9) In addition, individual differences suggest a pattern of mortality related to socioeconomic conditions, with worse rates among black or brown women and those with limited education. (4)(5)(6)(7)(8)(9) The Birth in Brazil Survey reinforced the differences in the adequacy of prenatal care in public services, revealing inequality in access to and quality of prenatal care among Brazilian regions.…”
Section: ❚ Introductionmentioning
confidence: 99%
See 1 more Smart Citation